COVID-19 Pandemic and Reduced Physical Activity: Is There an Impact on Healthy and Asthmatic Children? - Ferrante, Giuliana; Mollicone, Desiree; Cazzato, Salvatore; Lombardi, Enrico; Pifferi, Massimo; Turchetta, Attilio; Tancredi, Giancarlo; La Grutta, Stefania (Frontiers in Pediatrics, 2021)
Physical activity (PA) has been shown to improve asthma symptoms, lung function, and quality of life, as well as to reduce airway inflammation and bronchial responsiveness. Due to the COVID-19 pandemic, the minimal amount of PA recommended by World Health Organization -i .e. an average of 60 min/day of moderate-to-vigorous intensity- is difficult to achieve for many children, particularly those living in urban areas. Short-term changes in PA in reaction to the COVID-19 pandemic may become permanently entrenched, leading to an increased risk of adverse asthma outcomes in children. Indeed, the prolonged home confinement during the COVID-19 pandemic reduces PA levels and increases sedentary behaviors, which could impair the immune system function and raise the susceptibility to inflammatory diseases. However, limited evidence documented the effects of COVID-19-related lockdown on PA and sedentary behaviors in children with asthma. Given that children stay longer time indoors, indoor air pollution represents a relevant issue to consider during home confinement. This narrative review aims to summarize the available evidence about the impact of decreased PA and increased sedentary behaviors on children with asthma during the COVID-19 pandemic. In addition, strategies for supporting PA in children with asthma during the COVID-19 pandemic also looking at the issue of indoor air quality.